Bibliometric analysis of the top 100 most cited studies in apolipoprotein E (ApoE) research - Ahmad, Tauseef; Dhama, Kuldeep; Tiwari, Ruchi; Chaicumpa, Wanpen; Hui, Jin (Narra Sains Indonesia, 2021)
The apolipoprotein E (ApoE) is a glycoprotein which plays a vital role in different inflammatory conditions and in the catabolism of lipids and triglycerides. The aim of this study was to identify and evaluate the top 100 most cited studies on ApoE research. A bibliometric study was conducted. On January 18, 2021, studies published on ApoE were searched in the Web of Science Core Collection database without any limitations. The obtained data were analyzed for a number of attributes using HistCiteTM and VOSviewer software. The search yielded a total of 16,242 results. Of the total retrieved results, the top 100 most cited studies were selected. The top 100 most cited studies on ApoE were published from 1977 to 2017 and were cited 86,181 times. Single study citations ranged from 426 to 6,327. The studies were published in 41 journals authored by 589 authors. The study “Gene dose of apolipoprotein E type 4 allele and the risk of Alzheimer's disease in late onset families” was cited 6,327 times. Mahley RW, Roses AD, and Saunders AM were the most prolific authors who published ten studies each. Most of the studies were published in Proceedings of the National Academy of Sciences of the United States of America. A total of 151 institutions were involved, and the USA was the most productive country. Our finding provides valuable insight on ApoE research which may be useful for researchers, academia, and funding agencies to identify new future research domains.